PELATIHAN PENGGUNAAN MS POWER POINT SEBAGAI SARANA PEMBUATAN VIDEO PEMBELAJARAN PADA GURU MTS SIROJUL ATHFAL - Rina Mayanti; Ahmad Fauzi; Eko Harli; Michael Sonny (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
Schools need resources to rebuild lost in learning during this pandemic, learning innovations during the pandemic must be improved so that educational goals can still be achieved. Difficulties in making interactive learning media such as videos are the main problem for every teacher in providing learning innovations today, where every activity must comply with health protocols. This activity aims to provide training in making interesting learning videos, thereby increasing student interest in learning during the pandemic. This service activity is a workshop that will be held online. The results to be achieved in this activity are the increasing skills of MTs Sirojul Athfal teachers in making learning media in the form of videos using Ms Power Point